2013
DOI: 10.1038/bjc.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

DNA copy number profiling reveals extensive genomic loss in hereditary BRCA1 and BRCA2 ovarian carcinomas

Abstract: Background:Few studies have attempted to characterise genomic changes occurring in hereditary epithelial ovarian carcinomas (EOCs) and inconsistent results have been obtained. Given the relevance of DNA copy number alterations in ovarian oncogenesis and growing clinical implications of the BRCA-gene status, we aimed to characterise the genomic profiles of hereditary and sporadic ovarian tumours.Methods:High-resolution array Comparative Genomic Hybridisation profiling of 53 familial (21 BRCA1, 6 BRCA2 and 26 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…DLC1 and DLC2 copy number loss percentages in the TCGA breast carcinoma dataset were 33% and 18% respectively (data not shown). No DLC3 copy number losses were found in any of the tumors examined in this study, although losses at the DLC3/STARD8 locus at Xq13 have been reported in ovarian carcinomas [38]. As expected, copy number loss of DLC1 was found to be associated with its reduced expression.…”
Section: Discussionsupporting
confidence: 67%
“…DLC1 and DLC2 copy number loss percentages in the TCGA breast carcinoma dataset were 33% and 18% respectively (data not shown). No DLC3 copy number losses were found in any of the tumors examined in this study, although losses at the DLC3/STARD8 locus at Xq13 have been reported in ovarian carcinomas [38]. As expected, copy number loss of DLC1 was found to be associated with its reduced expression.…”
Section: Discussionsupporting
confidence: 67%
“…The profile of copy number variation (CNV) resembled those previously described for high-grade serous ovarian cancers [20, 21]. Given our targeted design, we focused on gene-specific CNVs of tumor suppressor genes TP53 , PTEN , RB1 , and NF1 , as well as genes involved in HR.…”
Section: Resultsmentioning
confidence: 99%
“…A series of 42 formalin‐fixed, paraffin‐embedded (FFPE) HGSOCs previously characterized using high‐resolution array CGH (4 × 180 K, Agilent Technologies, Palo Alto, CA) assuring >80% tumoral cellularity (Kamieniak et al., 2013) was included in the present study. Since the previous study (Kamieniak et al., 2013) aimed to characterize copy number changes in hereditary ovarian tumors and to describe similarities and differences with sporadic tumors the series comprised 30 familial and 12 sporadic HGSOCs. Inclusion of hereditary and sporadic cases in the current study allowed us to evaluate associations between the BRCA status and potential DNA copy number alterations predicting clinical outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The index case of each family was screened for mutations in the BRCA1 and BRCA2 genes by a combination of denaturing high performance liquid chromatography (DHPLC) and sequencing. Details about the screening of germline mutations in the BRCA1 and BRCA2 genes can be found elsewhere (Kamieniak et al., 2013). The 12 sporadic tumors (with no reported first or second degree relative with breast or ovarian cancer) were obtained from one hospital (H. Virgen del Rocio, Seville).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation